The Juridical Implications of an Acquittal for the Legal Protection of Children in Sexual Abuse Cases - Aftar akbar; Mulyati Pawennei; Nasrullah Arsyad (Al-Ishlah: Jurnal Ilmiah Hukum, 2025)
The acquittal verdict in cases of child sexual abuse has generated debate between the demand for victim protection and the principle of procedural justice in criminal procedural law. This study aims to analyze the juridical implications of acquittal decisions on child legal protection through an examination of the Parepare District Court Decision No. 61/Pid.Sus/2024/PN.Pre, which has obtained final legal force. The research employs a normative legal approach using statutory analysis and judicial decision review. Legal materials are analyzed qualitatively to assess the conformity of judicial reasoning with evidentiary principles under the Criminal Procedure Code (KUHAP) and the Child Protection Law. The findings indicate that the acquittal constitutes a juridical consequence of the failure to fulfill the elements of the offense and the absence of judicial conviction based on the evidentiary standard set forth in Article 183 of the KUHAP. The decision reflects the application of the presumption of innocence and the principle of in dubio pro reo, while simultaneously highlighting weaknesses in evidentiary quality in cases of sexual violence against children. This study emphasizes the need to strengthen investigations, scientific-based evidence, and inter-agency coordination to ensure effective child legal protection without undermining procedural justice for defendants